A-Kinase Interacting Protein 1 Promotes Cell Invasion and Stemness via Activating HIF-1α and β-Catenin Signaling Pathways in Gastric Cancer Under Hypoxia Condition - Luo, Zhenqin; Luo, Yuhang; Xiao, Ke (Frontiers in Oncology, 2022)
Background: A-kinase interacting protein 1 (AKIP1) relates to gastric cancer growth, metastasis and prognosis, while its regulation on gastric cancer invasion and stemness under hypoxia microenvironment is not reported. Therefore, this study aimed to explore this topic to uncover AKIP1’s role in gastric cancer under hypoxia. Methods: Gastric cancer cell lines AGS and MKN45 were cultured under hypoxia condition, then transfected with AKIP1 or negative control (NC) overexpression plasmid, AKIP1 or NC knock-down plasmid. Furthermore, rescue experiments were conducted by transfecting HIF-1α overexpression plasmid or β-catenin overexpression plasmid, combined with AKIP1 knock-down plasmid or NC knock-down plasmid. Afterward, cell invasion, CD133+ cell proportion, sphere number/1000 cells, HIF-1α and β-catenin pathways were measured. Results: The invasive cell count, CD133+ cell proportion, sphere number/1000 cells were enhanced in both AGS cells and MKN45 cells under hypoxia, and AKIP1 expression was also elevated. AKIP1 knock-down inhibited cell invasion, CD133+ cell proportion, sphere number/1000 cells, HIF-1α, VEGF, β-catenin and CBP expressions in AGS cells and MKN45 cells under hypoxia; while, AKIP1 overexpression presented with the opposite effect. Then in rescue experiments, HIF-1α overexpression and β-catenin overexpression both promoted cell invasion, CD133+ cell proportion and sphere number/1000 cells, which also attenuated the effect of AKIP1 knock-down on these functions in AGS cells and MKN45 cells. Conclusion: AKIP1 promotes cell invasion and stemness via activating HIF-1α and β-catenin signaling pathways in gastric cancer under hypoxia condition.